Waste heat recovery from thermo-electric generators (TEGs) - L. S. Hewawasam; A. S. Jayasena; M. M. M. Afnan; R. A. C. P. Ranasinghe; M. A. Wijewardane (Energy Reports, 2020)
Thermo-electric generators (TEGs) have been identified as promising solid-state devices to recover exhaust waste in internal combustion engines (ICEs). As the TEGs are able to convert heat directly into electricity, they can be used to down size the alternator of the ICEs. However, the addition of new devices to the engine exhaust system leads to increase the back pressure of the engine and reduces the overall efficiency of the engine. Therefore, this study is conducted to understand the possibility of integrating the TEG to the muffler of the engine, without interrupting the functionality of the muffler to recover the waste heat of the engine exhaust system. Findings of the study shows that the thermo-electric modules (TEMs) can be easily integrated to the muffler and electricity can be conveniently generated using the exhaust energy available in the hot exhaust gas.
Keywords: 330; Energy recovery; Availability; Exhaust system; Internal combustion engines; Thermo-electric generators